2020
DOI: 10.2147/dmso.s290491
|View full text |Cite
|
Sign up to set email alerts
|

The Association and Interaction of Aldehyde Dehydrogenase 2 Polymorphisms with Food Group Intake and Probability of Having Non-Alcoholic Fatty Liver Disease

Abstract: Purpose This study investigated the association between the aldehyde dehydrogenase 2 (ALDH2) rs671 polymorphism, food group intake, and the probability of having non-alcoholic fatty liver disease (NAFLD) in a Chinese population. Patients and Methods A total of 3506 adults were enrolled in this study, and all underwent physical examinations and genotyping of polymorphisms with polymerase chain reaction. Participants filled out a dietary questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Furthermore, Oniki et al reported that the ALDH2*2 allele significantly influences the risk for NAFLD [ 5 ]. Hao and Zeng showed that ALDH2 rs671 GA and AA genotypes are factors associated with increased NAFLD among Chinese subjects [ 6 ]. These results support a role for alcohol-metabolizing enzymes in NAFLD pathology, and further studies are needed to clarify the effects of NAFLD in alcohol metabolism and how alcohol affects NAFLD pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Oniki et al reported that the ALDH2*2 allele significantly influences the risk for NAFLD [ 5 ]. Hao and Zeng showed that ALDH2 rs671 GA and AA genotypes are factors associated with increased NAFLD among Chinese subjects [ 6 ]. These results support a role for alcohol-metabolizing enzymes in NAFLD pathology, and further studies are needed to clarify the effects of NAFLD in alcohol metabolism and how alcohol affects NAFLD pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, cumulative evidence has revealed that ALDH2 plays an important role in liver diseases associated with the autophagy signal pathway ( 27 , 28 ). ALDH2 could ameliorate chronic alcohol intake-induced hepatic steatosis and inflammation through the regulation of autophagy ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study show that the rs671 polymorphism genetically modifies the association between DBs and BMI. Recently, interactions between the rs671 polymorphism and DBs have been reported in several diseases, such as hypertension [ 23 , 24 , 25 ], coronary artery disease [ 21 ], and non-alcoholic fatty liver disease [ 28 ]. However, the three-way association among the rs671 polymorphism, DBs, and BMI as a health indicator in general population remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Carriers of the A allele of the rs671 polymorphism with drinking habit were at a higher risk of several cancers than carriers of the G allele [ 15 , 16 , 17 , 18 ]. Furthermore, it has been reported that interaction between the rs671 polymorphism and consumption of fried foods in hypertension [ 24 , 25 ] and in coronary artery disease [ 21 ], and interactions between the polymorphism and the consumption of fresh fruits, vegetables, and salted and smoked foods in nonalcoholic fatty liver [ 28 ]. However, it is unclear whether the rs671 polymorphism genetically modifies the association between DBs and an outcome, and no information has been presented to indicate what DBs are recommended for health for each rs671 genotype.…”
Section: Introductionmentioning
confidence: 99%